Southeastern United States wood pellets as a global energy resource: a cradle-to-gate life cycle assessment derived from empirical data - Brandon Morrison; Jay S. Golden (International Journal of Sustainable Energy, 2018)
Given increased policies driving renewable electricity generation and insufficient local production of woody biomass, many countries are reliant upon the importation of wood pellets. Of current wood pellet exports, the vast majority originates from the Southeastern United States (US). In this paper we present results from a cradle-to-gate, attributional process life cycle assessment in which two production scenarios of wood pellets were modelled for the Southeastern US: one utilising roundwood from a silviculture operation and the other utilising sawmill residues. The system boundary includes all steps from harvesting of the wood biomass, through delivery of the finished wood pellets to a US port facility. For each of the impact categories assessed, wood pellets from sawmill residues resulted in higher values, ranging from 5% to 31%. In relation to Global Warming Potential, roundwood pellets resulted in a 13–21% lower value than pellets produced from sawmill residues, depending upon the allocation method.